KALIMAT TANYA DALAM NOVEL THE GUARDIAN KARYA NICHOLAS SPARKS - Rondonuwu, Melanny (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT   This study entitled The ‘Interrogative Sentence in The Novel The Guardian by Nicholas Sparks’ is aimed at identifying and analyzing the interrogative sentence found in the novel. The data have been collected by focusing on the conversation among the characters in the novel and analyzed them based on Aarts and Aarts concept. The result shows that interrogative sentence in English are three kinds those are yes/no question, question tag, wh-question. In this novel the author uses interrogative sentence without question word. According to its function in communication, interrogative sentence can be functioned as question and request. -------------------------------------------------------------------------- Keywords: interrogative sentence, grammatical analysis, Novel The Guardian